3D GRAPHICS AND VIRTUAL REALITY TECHNOLOGIES IN FINE ARTS - Orinov Muhammadjon Khojakbar ogli (Web of Journals Publishing, 2025)
This article explores the application of 3D graphics and virtual reality (VR) technologies in contemporary fine arts. It examines how these technologies are reshaping artistic practice, offering new modes of visual expression, audience interaction, and narrative construction. The study highlights the conceptual and aesthetic potentials of 3D and VR in creating immersive experiences, expanding the spatial and sensory dimensions of art. Furthermore, the article analyzes how these technologies influence art education, interdisciplinary collaboration, and the evolution of visual culture in the digital era.
Keywords: 3D graphics, virtual reality, fine arts, immersive art, digital sculpture, interactive art, contemporary art, new media, digital aesthetics, spatial experience.